Camphor Tree (Dryobalanops Aromatica) Bark Extract As Corrosion Inhibitor For Mild Steel In Acidic Medium - Akuben, Yakubu Saraya (2021)
The goal of the study is to extract tannin from the bark of camphor tree (Dryobalanops aromatica) and to study the corrosion inhibition potential of the tannin extracts on mild steel in 0.5 M HCl. The extraction was carried out through maceration, gave percentage yield in the order of methanol extract > water extract > ethyl acetate extract > hexane extract. The tannin methanol extract (TME) and tannin water extract (TWE) further characterized qualitatively and quantitatively. The Fourier transformed infrared spectroscopy (FTIR) spectra for both extracts revealed the presence of functional groups that characterise good corrosion inhibitor. The carbon-13 nuclear magnetic resonance (13C NMR) showed that both TME and TWE contain carbon-13 signals for procyanidin tannin. The total phenolic content (TPC) carried out by Folin-Ciocalteau method, total flavonoid content (TFC) by aluminium chloride colorimetric method, total tannin content (TTC) assay by Stiasny method were found to be higher in TME than TWE. The antioxidant assays revealed that TME has more reducing and antiradical power than TWE. The results from the corrosion inhibition studies conducted via electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PD) and electrochemical noise (EN) techniques showed that, inhibition efficiencies (IE) of TME and TWE increased with concentration up to 1000 ppm and the IE from the three different techniques were within the range of 80 - 93 % for TME and 80 - 92 % for TWE. All the experimental data for both tannin extracts fitted best into the Langmuir adsorption isotherm and physisorption mechanism described the inhibition process.